2008
DOI: 10.1123/shr.39.1.45
|View full text |Cite
|
Sign up to set email alerts
|

R. Tait Mckenzie’s Medical Work and Early Exercise Therapies for People with Disabilities

Abstract: I showed [McKenzie] a letter I had received from a rising man in our profession who wanted to know what I could tell him about Dr. Luther Gulick.. .. McKenzie's comment was that it was strange that a man who had done so much for us should be forgotten so soon. "I guess," he said, "that this will happen to all of us so far as our work in physical education is concerned. And if it is not entirely forgotten, our endeavors most likely will be misunderstood or misconstrued by persons who will not try to understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Mason (2008) has suggested that McKenzie, like many other physical educators, felt "athletics" was contraindicated as a form of rehabilitation because the competitive element would lead to too much strain and overexertion; similarly he was concerned with women overexerting themselves. Through orthopaedics and treatment of spinal curvatures such as scoliosis with exercise, he advocated exercise both as a preventative treatment and as a form of rehabilitation.…”
Section: Mckenzie the Physical Educator And Advocate Of Remedial Physmentioning
confidence: 99%
See 4 more Smart Citations
“…Mason (2008) has suggested that McKenzie, like many other physical educators, felt "athletics" was contraindicated as a form of rehabilitation because the competitive element would lead to too much strain and overexertion; similarly he was concerned with women overexerting themselves. Through orthopaedics and treatment of spinal curvatures such as scoliosis with exercise, he advocated exercise both as a preventative treatment and as a form of rehabilitation.…”
Section: Mckenzie the Physical Educator And Advocate Of Remedial Physmentioning
confidence: 99%
“…The use of exercise for those with a physical disability was pioneering and the subject of many of his publications, as was his thinking about urbanisation and structuring the school day so that children had sufficient exercise (Mason, 2008). But these contributions reflect the "discourse" of that era.…”
Section: Mckenzie the Physical Educator And Advocate Of Remedial Physmentioning
confidence: 99%
See 3 more Smart Citations